Macroporous dehydroalanine polymer hydrogel with fast temperature response and high repetition durability. Issue 1 (16th April 2012) - Tezuka, Yoshihiko; Tanaka, Hitoshi
Abstract Thermoresponsive hydrogels based on poly(methyl 2‐isobutyramidoacrylate) (PMIBA) were prepared by free‐radical crosslinking polymerization of the corresponding monomer using N, N′‐methylenebisacrylamide as a crosslinker. The PMIBA hydrogels showed a reversible temperature‐induced volume change with a volume phase transition temperature (VPTT) at 19°C, while they contained more than 60 wt % water even in the equilibrium deswollen state. When the external temperature was raised rapidly above the VPTT, the PMIBA gels shrank smoothly with time at a faster rate than conventional poly(N‐isopropylacrylamide) hydrogels of the same size. The fast and smooth deswelling response of the PMIBA gel is ascribed to its sponge‐like structure with 0.1–1 µm pore sizes formed in the deswollen state. The smooth deswelling response due to the macroporous structure resulted in high durability against repeated changes in the external temperature. The PMIBA gel showed little degradation in the swelling ability when subjected to 50 times of thermal cycling across the VPTT. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2012